BAURAN PEMASARAN KEPUASAN DAN LOYALITAS PELANGGAN BENIH KELAPA SAWIT PT SOCFIN INDONESIA - Safitri, Sri Ariani; Suharno, Suharno; Fariyanti, Anna (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
Along with the increasing demand of palm oil seed trigger an increased number of seed producers of palm oil in Indonesia. Under conditions of tight competition, PT Socfin Indonesia (Socfindo) as one of the producers of palm oil seed needs to evaluate the performance of the marketing mix (product, price, place and promotion) through customer satisfaction and loyalty. This study aimed to analyze the influence of marketing mix towards customer satisfaction and loyalty as well as to analyze the level of satisfaction and loyalty customerÃ‚Â palm oil seed of PT Socfindo. The collection of data through the 30 respondent companies. Data analysis methods used Structural Equation Model Partial Least Square (SEM PLS). Analysis results showed that the the product variables have a significant influence on customer satisfaction and loyalty, while the variables of price, place and promotion does not have a significant influence in shaping customer satisfaction and loyalty. In addition, the calculation results Customer Satisfaction Index (CSI), customer satisfaction index palm oil seed PT Socfindo which can be categorized as very satisfied and calculating results Customer Loyalty Index (CLI), an index of customer loyalty palm oil seed PT Socfindo which can be categorized loyal.